Intensive smoking cessation intervention in a nature-based setting: a feasibility study of the Danish gold standard program - Mie Sylow Liljendahl; Sanne Staal; Hanne Tønnesen (Frontiers in Public Health, 2025)
The implementation of nature-based interventions has demonstrated a positive impact on health outcomes and overall wellbeing. The knowledge of nature-based smoking cessation interventions is sparse but might offer potential benefits for smokers undertaking an intensive smoking cessation program. This study assessed the feasibility in real life of the 6-week Danish Intensive Gold Standard Program (GSP) for smoking cessation in nature compared to the standard setting in primary healthcare. This feasibility study followed up with 81 out of 90 (90%) participants in a nature-based setting and 56,480 out of 58,772 (96%) participants in a standard setting. All participants received the intensive GSP and were registered after providing informed consent in the national Danish STOPbase between 2018 and 2023. Feasibility was assessed using the following indicators: primarily successful quitting after 6 months, secondarily at the end of the 6-week program, as well as compliance and satisfaction—all obtained through interviews. All indicators were similarly high in both settings. After 6 months, 43% had successfully quit in the nature-based setting and 37% in the standardized setting without statistical significance (RR 1.25, 95% CI: 0.80–1.94). The nature-based setting was feasible and appeared to produce similar outcomes as the standard setting for the 6-week intensive GSP in Denmark in real life.